2014
DOI: 10.1016/j.colsurfb.2014.06.026
|View full text |Cite
|
Sign up to set email alerts
|

AFM in mode Peak Force applied to the study of un-worn contact lenses

Abstract: Contact lenses (CLs) are of common use and the biocompatibility, topography and mechanical properties of the used materials are of major importance. The objective of this contribution is to apply the AFM in mode Peak Force to obtain surface topography and mechanical characteristics of un-worn CLs of different materials. One material of hydrogel, two of siloxane-hydrogel and one of rigid gas permeable, were used in the There is no significant influence of the environment, water or saline solution, on the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Also, as it is mentioned before, fullerene unlike its derivates, fullerol and methformin hydroxylate fullerene, does not dissolve in water and certain solvents. Topographic analysis in this study dealing with the hydrogel SCL type was comparable with values reported in the literature [53][54][55][56][57]. The inhomogeneity may originate as a consequence of processing, showing that some parts of surface had polymers with altered conformation states, thereby expressing different intermolecular interactions.…”
Section: Resultssupporting
confidence: 82%
“…Also, as it is mentioned before, fullerene unlike its derivates, fullerol and methformin hydroxylate fullerene, does not dissolve in water and certain solvents. Topographic analysis in this study dealing with the hydrogel SCL type was comparable with values reported in the literature [53][54][55][56][57]. The inhomogeneity may originate as a consequence of processing, showing that some parts of surface had polymers with altered conformation states, thereby expressing different intermolecular interactions.…”
Section: Resultssupporting
confidence: 82%
“…The characteristics of un-worn P and AO CLs were studied in a previous work [12], and they are summarized in Table 1 for the case of being immersed in saline solution. Figure 1 shows the AFM topographic images of several worn CLs, corresponding to several subjects, for both Si-H CL types.…”
Section: Resultsmentioning
confidence: 99%
“…For the topographic analysis, four parameters have been used [20]: mean roughness (Ra), root-mean-square roughness (RMS or Rq), skewness (Rsk) and kurtosis (Rku). More details were reported in reference [12].…”
Section: Afm Technique and Equipmentmentioning
confidence: 99%
See 2 more Smart Citations